2018
DOI: 10.1038/s41580-018-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and medical implications of mammalian autophagy

Abstract: Autophagy is a highly conserved catabolic process induced under various conditions of cellular stress, which prevents cell damage and promotes survival in the event of energy or nutrient shortage and responds to various cytotoxic insults. Thus, autophagy has primarily cytoprotective functions and needs to be tightly regulated to respond correctly to the different stimuli that cells experience, thereby conferring adaptation to the ever-changing environment. It is now apparent that autophagy is deregulated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
1,965
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,233 publications
(1,998 citation statements)
references
References 201 publications
20
1,965
0
13
Order By: Relevance
“…Under nutrient replete conditions, mTORC1 phosphorylates ULK1 and ATG13, inhibiting autophagy initiation . On starvation, ULK1 is dephosphorylated followed by autophosphorylation and phosphorylation of ATG13 and FIP200, leading to a rapid induction of autophagy . Furthermore, autophagy can be enhanced as well by an energetic stress response mediated by the AMP‐activated protein kinase (AMPK).…”
Section: Role and Regulation Of Autophagy In Cancermentioning
confidence: 99%
“…Under nutrient replete conditions, mTORC1 phosphorylates ULK1 and ATG13, inhibiting autophagy initiation . On starvation, ULK1 is dephosphorylated followed by autophosphorylation and phosphorylation of ATG13 and FIP200, leading to a rapid induction of autophagy . Furthermore, autophagy can be enhanced as well by an energetic stress response mediated by the AMP‐activated protein kinase (AMPK).…”
Section: Role and Regulation Of Autophagy In Cancermentioning
confidence: 99%
“…5 LBH589 (panobinostat), a non-selective histone deacetylase inhibitor (pan-HDAC inhibitor), has been shown to induce tumour shrinkage and sustain stable disease status in a phase II trial of pre-treated lung cancer patients. 8,9 BNIP3 (Bcl-2/adenovirus E1B 19 kD protein-interacting protein 3) is a pro-cell death member of the Bcl-2 family and contains only the BH3 domain. 7 Autophagy is a self-digesting catabolic process induced under various stress conditions for homoeostatic cellular recycling that has been implicated in the progression of many diseases, including cancer and neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Another physiological cellular process involved in this mechanism is autophagy, which is one route of lysosome degradation that regulates cellular lipid metabolism and controls the innate immune activation, improving the state of insulin resistance and cancer (Dikic and Elazar, 2018[7]). Several works reported the beneficial effects of autophagy in carcinogenesis and studies of GLP-1 analogs have shown its ability to increase autophagy (He et al, 2016[12]; Li et al, 2017[17]).…”
Section: Discussionmentioning
confidence: 99%